La valutazione psicologica: dal colloquio clinico alla stesura di un report diagnostico in chiave Gestaltica integrata - 1Viviana Catania, 1Sebastiana Cipponeri, 1Lorena Vincenza Perrone (Phenomena Journal)
There have been several authors who in recent years have sought to clarify the world of psychodiagnosis: from the analysis of expert question to the criminological interview, from the structure of expert report to the development of new damage assessment criteria. Also in the testological field, numerous researches have highlighted how the appropriate use of tests represents one of main sides in the evaluation process. Latest studies in literature have been and are an important guide to interpretation and reporting both in the clinical and legal-expert field of the MMPI-2 (Minnesota Multiphasic Personality Inventory-2), integrating insights related above all to its restructured form (MMPI-2 RF). It becomes important, in fact, that there is attention in choice of tools not only "technical" but also "relational", in order to constitute an "appropriate frame of meaning", necessary for a careful and scrupulous psychological evaluation. Within the scientific panorama main objective of the authors, after having performed a detailed and in-depth analysis of the literature in question, will be to propose through this contribution, a practical guide to outline the "good practices" indispensable for each type of intervention, in order to be able to conduct a Gestaltic psychological assessment (from the clinical interview to the collection of bio / psycho / social data up to the correct administration of the psychological tests) in the various professional fields (clinical, expert, etc.).